Optimization of micro processes in fine particle agglomeration by pelleting flocculation : a thesis approved by the faculty of Environmental Sciences and Process Engineering at the Brandenburg University of Technology in Cottbus in partial fulfilment of the requirement for the award of the academic degree of Doctor of Philosophy (Ph. D.) in Environmental sciences /: a thesis approved by the faculty of Environmental Sciences and Process Engineering at the Brandenburg University of Technology in Cottbus in partial fulfilment of the requirement for the award of the academic degree of Doctor of Philosophy (Ph. D.) in Environmental sciences. ([2016]) - Oyebgile, Benjamin A
No abstract available